“Santorio and Leibniz on Natural Immortality: The Question of Emergence and the Question of Emanative Causation.” - Blank, Andreas (Santorio Santori and the Emergence of Quantified Medicine.)

“Common Notions and Immortality in Digby and the Early Leibniz.” - Blank, Andreas (The Philo-sophy of Kenelm Digby (1603–1665).)

Rezension von Martin Mulsow und Asaph Ben-Tov (eds.), Knowledge and Profanation. Transgressing the Boundaries of Religion in Pre-Modern Scholarship - Blank, Andreas (Quellen und Forschungen aus italienischen Archiven und Bibliotheken)

“Jacob Schegk on Plants, Medicaments and the Question of Emergence.” - Blank, Andreas (Mechanism, Life and Mind in Modern Natural Philosophy.)

“Julius Caesaer Scaliger.” - Blank, Andreas (Encyclopedia of Renaissance Philosophy)

Fortunio Liceti - Blank, Andreas (Encyclopedia of Renaissance Philosophy)

“Pharmacology in the Renaissance.” - Blank, Andreas (Encyclopedia of Renaissance Philosophy)

„Die Räume richtig auseinanderhalten“. Anmerkungen zum Politischen im Gegenwartstheater. - Eke, Norbert (Wege der Germanistik in transkultureller Perspektive. Akten des XIV. Kongresses der Internationalen Vereinigung für Germanistik (IVG))

Du Châtelet's Libertarianism - Wells, Aaron (History of Philosophy Quarterly)
Abstract There is a growing consensus that Emilie Du Châtelet's challenging essay “On Freedom” defends compatibilism. I offer an alternative, libertarian reading of the essay I lay out the prima facie textual evidence for such a reading. I also explain how apparently compatibilist remarks in “On Freedom” can be read as aspects of a sophisticated type of libertarianism that rejects blind or arbitrary choice. To this end, I consider the historical context of Du Châtelet's essay, and especially the dialectic between various strands of eighteenth-century libertarianism and compatibilism.
Keywords: Philosophy

Science and the Principle of Sufficient Reason: Du Châtelet contra Wolff - Wells, Aaron (HOPOS: The Journal of the International Society for the History of Philosophy of Science)
Keywords: History and Philosophy of Science

Incompatibilism and the Principle of Sufficient Reason in Kant’s Nova Dilucidatio - Wells, Aaron (Journal of Modern Philosophy)
Keywords: Automotive Engineering

Jörg Noller and John Walsh (eds), Kant’s Early Critics on Freedom of the Will Cambridge: Cambridge University Press, 2022 Pp. xlvii + 315 ISBN 9781108482462 (hbk) £74.99 - Wells, Aaron (Kantian Review)
Keywords: Philosophy

Soigner l’humain Péchés et remèdes chez Montaigne et Descartes - Muller, Jil

Editorial - Taschl-Erber, Andrea; Guanzini, Isabella; Hable, Ingrid (LIMINA – Grazer theologische Perspektiven)

Fragile Ordnungen – Heimatkonstruktionen im Ausnahmezustand in Doron Rabinovicis „Die Außerirdischen“ - Willeke, Stephanie (Aussiger Beiträge)

Verbally Resisting Taxes in Medieval England. Arguments, Anger and the (In)Ability to Prevent Tax Avoidance in the Reign of Henry III - Bröker, Christina (Histories of Tax Evasion, Avoidance and Resistance)

Die Auswirkungen von digitalen Plattformen auf ökologische Herausforderungen - Ein systematischer Literaturüberblick - Bradaric, Daniel

“Christoph Besold on Confederation Rights and Duties of Esteem in Diplomatic Relations.” - Blank, Andreas (Intellectual History Review)

“Pufendorf and Leibniz on Duties of Esteem in Diplomatic Relations.” - Blank, Andreas (Journal of International Political Theory)

“Esteem and Self-Esteem in Early Modern Ethics and Politics. An Overview.” - Blank, Andreas (Intellectual History Review)